Analgesics for Dental Implants: A Systematic Review - Matteo Melini; Andrea Forni; Francesco Cavallin; Matteo Parotto; Gastone Zanette (Frontiers Media S.A., 2021)
Postsurgical pain is commonly associated with dental and oral surgery, and the use of analgesics has been investigated in the management of postoperative pain. This systematic review summarizes available evidence on analgesics used to manage dental implant surgery postoperative pain, to identify best therapeutic protocols and knowledge gap. A comprehensive search was conducted including MEDLINE/Pubmed, EMBASE, SCOPUS, clinicaltrials.gov, and the Cochrane Database of Systematic Reviews through May 2020. Only randomized controlled trials were included. PRISMA guidelines were followed, and risk of bias was appraised using Cochrane RoB2 tool. Eleven trials (762 patients overall) were included. Some aspects limited the feasibility of a meaningful meta-analysis; thus, a narrative synthesis was conducted. Risk of bias was low in four studies and high in two studies, while five studies raised some concerns due to the randomization process. Analgesic use seemed to be associated with improved postoperative outcomes (pain, patient's satisfaction, and need for rescue medication) when compared to placebo. Overall, this review suggests that the administration of analgesics may provide some advantages in the management of postoperative outcomes after dental implant placement, while indications about the best analgesics cannot be provided.